Impacts of terminal velocity on precipitation prediction and the error representation of terminal velocity in ensemble forecasts - Shizhang Wang; Xiaoshi Qiao (Atmospheric Science Letters, 2020)
Abstract Impacts of terminal velocities (rainwater, snow, and hail) on precipitation and the representation of terminal velocity uncertainty in ensemble forecasts were discussed in several idealized scenarios differing in intercept parameters and environmental soundings. In this idealized case, the precipitation maximum and cold pool were sensitive to the rainwater terminal velocity, while the precipitation coverage was sensitive to terminal velocities of ice‐species. Although precipitation maximum approximately increased with terminal velocity, pronouncedly large terminal velocity may form a cold pool too weak for precipitation system development. The main finding for ensemble forecasts is that allowing for terminal velocity uncertainty in ensemble forecasts could benefit the precipitation forecast skill; using perturbations based on the terminal velocity bias of each species improved the forecast skill in more scenarios than using the same perturbation for all species.